PENGEMBANGAN MEDIA PEMBELAJARAN FLIPBOOK DIGITAL PADA ELEMEN MEMBACA CERITA RAKYAT SISWA KELAS IVB SDN 2 MEURANDEH - Natasya Sihombing, Indah; Mulyahati, Bunga; Febri Rafli, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop digital flipbook learning media on the element of reading folk tales for fourth-grade students of SDN 2 Meurandeh and to determine the level of feasibility and practicality in the learning process. This study uses the Research and Development (R&D) type with the ADDIE model consisting of the stages of analysis, design, development, implementation, and evaluation. The subjects of the study were fourth-grade students of SDN 2 Meurandeh. Data collection techniques were carried out through observation, interviews, and questionnaires. The instruments used included validation questionnaires from material experts, media experts, linguists, and student and teacher response questionnaires. Data were analyzed qualitatively and quantitatively using a Likert scale. The results of the study showed that the developed media obtained a validation percentage of material experts of 83.33%, linguists of 88.88%, and media experts of 88.33% with very feasible criteria. In addition, the results of the practicality test showed a percentage of student responses of 89.2% and teacher responses of 86.66% with very practical criteria. The developed digital flipbook media is able to make learning more interesting and help students understand the material of reading folk tales. Thus, this media can be used as an alternative medium for Indonesian language learning in elementary schools.